Views of Hospital Nurses and Nursing Students on Nursing Engagement—Bridging the Gap Through Communication Courses - Huang, Qing; Pun, Jack (Frontiers in Psychology, 2022)
Communicative engagement is central for effective nurse-patient communication. In the existing college nursing communication training within and outside China, there are divergences between what students are taught and what they can apply in their clinical placements. Using needs analysis, this mixed-methods study explored potential gaps between frontline hospital nurses’ and college nursing students’ perceptions of nurse-patient communicative engagement, and collated a list of effective engagement strategies for pedagogy. Surveys and interviews were conducted with key stakeholders, including sixteen hospital nurses and sixty nursing students. A new scale named Nursing Engagement with Patients Scale (NEPS) was developed and validated to explore stakeholders’ views on nursing engagement. Differences between the nurses’ and students’ views on engagement were identified. While frontline nurses affirmed the importance of engaging with patients while providing nursing care, nursing students were unsure about the concept and role of engagement, and how to enact it. A list of communication strategies that promote engagement was culled from the interviews with the experienced nurses. These can be used to inform nursing communication courses to bridge the gap between what nursing students are currently taught and what they will need in the workplace.